G151 Characteristics and outcomes in children with sickle cell disease and severe occlusive cerebral arteriopathy referred for neurological evaluation. (May 2019) - Lu, B; Toolis, C; Thompson, D; Ganesan, V
Abstract : Aims: To describe children with sickle cell disease (SCD) referred to multidisciplinary revascularisation service at our centre for consideration of neurosurgical revasculariation. Methods: Retrospective notes/imaging review. Results: Between 2007–2017, consistent criteria were used to offer revascularisation in SCD, namely recurrent clinical or radiological ischaemic events despite optimal medical management. Thirty-one children (median age 16.4 years) had been seen; 12 had had prior arterial ischaemic stroke (AIS) or transient ischaemic attack (TIA). 13 had abnormal transcranial Dopplers (TCD) and two had had silent cerebral infarction (SCI) on imaging. 11 children were referred purely based on abnormal TCD/MRI without clinical events. Twenty-six children were on chronic transfusion therapy (CTT), 24 had had recurrent events. 28 had intracranial and 5 had extracranial arteriopathy on magnetic resonance angiography. 11/31 children (15 hemispheres) underwent revascularisation; another 3 patients were offered but declined. All had had clinical and/or radiological progression on CTT. The rest were not offered surgery because of stability or potential to optimise medical management. Surgical complications included one wound infection and one post-operative TIA. Median follow-up was nine months; patients who had surgery were followed up for significantly longer (p=0.03). AIS-free survival at initial assessment was not significantly different between surgery and no-surgery groups. Significantly more children in the surgery group (p=0.023) experienced clinical events during follow-up. Conclusion: Patients currently referred for revascularisation have a high rate of recurrent events despite CTT. Some of those who were offered surgery, assessed as the highest risk group, had further events despite this. AIS-free survival at initial assessment was not significant between groups, thus current threshold for revascularisation, namely recurrence on CTT, could be too high. The higher rate of events in the surgery vs. no-surgery group is likely related at least partly, to lack of follow-up in the latter. Consensus criteria for referral and intervention would assist systematic prospective data collection.